2003
DOI: 10.1177/1090198102239260
|View full text |Cite
|
Sign up to set email alerts
|

“If They Don’t Ask About Condoms, I Just Tell Them”: A Descriptive Case Study of Latino Lay Health Advisers’ Helping Activities

Abstract: Health care practitioners have increasingly turned to lay health advisers (LHAs) to deliver health promotion and disease prevention supportive activities to underserved populations. Yet, published evaluations of the LHA programs or the manner in which LHAs deliver information are rare. An important aspect of program evaluation includes understanding the role of the LHA in the community as described by the LHAs in the field. The purpose of this article is to report the results of a component of a larger evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 35 publications
0
31
0
Order By: Relevance
“…Using more informal labels which do not denote responsibility and commitment, as one BHA suggested, may reduce this barrier. Interestingly, other programs have reported that lay health advocates felt a sense of expertise [16], so providing formal recognition of training such as a program completion certificate may help build confidence [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using more informal labels which do not denote responsibility and commitment, as one BHA suggested, may reduce this barrier. Interestingly, other programs have reported that lay health advocates felt a sense of expertise [16], so providing formal recognition of training such as a program completion certificate may help build confidence [24].…”
Section: Discussionmentioning
confidence: 99%
“…Programs using lay health advocates, also known lay health workers, peer educators or natural helpers [14], have been employed for a variety of health education interventions around the world [15]. Such interventions have the potential to empower lay health advocates and their community [16], as indicated by findings of increases in advisor knowledge and increased community use of preventive health services [17]. To our knowledge, this is the first culturally specific breast health and screening promotion program for Chinese-Australian women in Australia.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, Rhodes and colleagues carried out a systematic review of published studies on CHWs among Latino communities and described one of the six primary roles of CHWs as ''co-researchers in participatory research models'' [11], noting specific studies where CHWs served as integral members of the research team [12][13][14][15][16][17][18][19][20]. On the other hand, Rosenthal and colleagues identify data collection as a core role of CHWs, but did not identify research skills as a core competency of CHWs [21].…”
Section: Introductionmentioning
confidence: 99%
“…The benefits associated with lay involvement includes diverse range of claims, from assumptions about increased coverage and efficiency of services (18) increased efficacy in changing health related behaviours (19)(20)(21) particularly amongst the so-called 'hard-to reach' groups (21), individual or community empowerment (22,23) and advocacy on behalf of socially disadvantaged or ethnic minority communities (24). Evidently, social affinity and unique ability of lay people, particularly those indigenous to the communities served, to disseminate culturally specific messages and help in identifying and overcoming barriers to behaviour change, is key to their success (25,26,27 In essence public health claims to be concerned with the health and wellbeing of populations.…”
Section: Introduction and Background (970)mentioning
confidence: 99%